# How do you solve #3x + 2y = -12# for y?

Your explanation of solving the equation for y didn't quite make sense to me, but I suppose it would work like this:

By signing up, you agree to our Terms of Service and Privacy Policy

To solve for ( y ), rearrange the equation to isolate ( y ):

[ 3x + 2y = -12 ]

[ 2y = -12 - 3x ]

[ y = \frac{-12 - 3x}{2} ]

[ y = \frac{-12}{2} - \frac{3x}{2} ]

[ y = -6 - \frac{3x}{2} ]

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7